A Cultural overview on the concept of infinity - Di Sia, Paolo (Journal of Education Culture and Society, 2019)
Abstract: The human being meets the idea of infinity very early, still a child, when he  realises that he can go on counting using  natural numbers until it is impossible to continue to count. The idea of infinity attracts and rejects, sometimes becomes an  object of desire and sometimes of study and systematic research. Infinity is the testimony that intellect, even starting from experience, can overcome limits and boundaries. Our own limited experience on the Earth suggests the existence of something beyond it. Scientists, artists, philosophers, musicians, writers, mathematicians have often assumed towards this concept positions and opinions sensitively different. Infinity would be, by its etymology and nature, what escapes all possible classification and measurement, while mathematics tends to classify and measure every object it examines, and  has been able to measure it. Infinity follows us from primary school until university, but often remains a misunderstood concept in the mathematical sense.